Implementation of Laboratory Equipment Loan System in SiDal (BigData Laboratory System): Penerapan Sistem Peminjaman Alat Laboratorium pada SiDal (Sistem BigData Laboratorium) - Cahyo Puji Asmoro; Hana Susanti; Iin Maemunah (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2023)
Borrowing and returning equipment for both practicum and research is one of the routine laboratory management activities. Laboratories with a high intensity of borrowing equipment but limited human resources should use an online information system to manage the flow of borrowing so that laboratory activities can run optimally. This research was made based on these problems encountered in laboratory management at the Basic Physics Laboratory (LFD) of Universitas Pendidikan Indonesia (UPI). Previously, research was conducted on the development of a laboratory information system named SiDal (Laboratory BigData System). In SiDal, users can access tool data, tool catalog, tool status and tool storage. From the catalog of tools stored in SiDal as a data base, a system for borrowing and returning laboratory equipment was developed and then the application of this system was tested at LFD FPMIPA UPI. Through research and development methods, surveys were conducted through questionnaires and written interviews. From the results of the questionnaire distributed, 52 student respondents from various batches who had accessed SiDal showed that around 90% said that the loan system developed was more effective & practical, which was confirmed from the results of written interviews. Abstrak Peminjaman dan pengembalian alat baik untuk praktikum maupun penelitian merupakan salah satu dari kegiatan pengelolaan laboratorium yang rutin dilakukan. Laboratorium dengan intensitas peminjaman alat yang tinggi namun sumber daya manusia yang terbatas sebaiknya sudah menggunakan sistem informasi online untuk melayani alur peminjaman, agar kegiatan laboratorium dapat berjalan optimal. Penelitian ini dibuat berdasarkan permasalahan tersebut yang ditemui dalam pengelolaan laboratorium di Laboratorium Fisika Dasar (LFD) Universitas Pendidikan Indonesia (UPI). Sebelumnya sudah dilakukan penelitian tentang pengembangan sistem informasi laboratorium yang diberi nama SiDal (Sistem BigData Laboratorium). Dalam SiDal, pengguna dapat mengakses data alat, katalog alat, status alat berikut tempat penyimpanan alat. Dari katalog alat yang disimpan di SiDal sebagai database, dikembangkan sistem peminjaman dan pengembalian alat laboratorium kemudian di Uji coba kembali penerapan sistem ini di LFD FPMIPA UPI. Melalui metode penelitian dan pengembangan, dilakukan survey melalui angket dan wawancara tertulis. Dari hasil angket yang disebar didapat 52 responden mahasiswa dari berbagai angkatan yang pernah mengakses SiDal menunjukan sekitar 90 % menyampaikan bahwa sistem peminjaman yang dikembangkan lebih efektif & praktis yang dipertegas dari hasil wawancara tertulis.